Guava Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
Revised! HS-4, a 10-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a greatly expanded (from the previous 2-page fact sheet) basic reference for growing guava in the home landscape. Additional tables include information on guava varieties for Florida, cultural practices by month, fertilizer program, and nutritional values. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005.